2017
DOI: 10.1097/md.0000000000009001
|View full text |Cite
|
Sign up to set email alerts
|

Primary intramedullary primitive neuroectodermal tumor

Abstract: Rationale:Primary spinal primitive neuroectodermal tumors (PNETs) are highly malignant tumors, which are extremely rare entities and primary intramedullary PNETs are extremely rare. Till now, only 24 cases of primary intramedullary PNET have been reported.Patient concerns:A 26-year-old male presented with progressive low back and lower limb pain for 1 month.Diagnoses:Based on MRI and histopathological findings, he was diagnosed with primary intramedullary PNET.Interventions:The patient was treated two times wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The identified cases showed that intramedullary Ewing sarcoma was located mainly in the thoracic and lumbar regions, although cervical and sacral locations were also reported. 4 36 The current case had a thoracic intramedullary lesion and a lumbar extramedullary lesion, both causing neural compression and deficits.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The identified cases showed that intramedullary Ewing sarcoma was located mainly in the thoracic and lumbar regions, although cervical and sacral locations were also reported. 4 36 The current case had a thoracic intramedullary lesion and a lumbar extramedullary lesion, both causing neural compression and deficits.…”
Section: Discussionmentioning
confidence: 87%
“… 2 The prognosis and survival rate for patients with spinal cord Ewing sarcoma is not well known because of the rarity of the condition; however, based on previous cases ( Table 1 ), the survival rate was 45% to 50% in primary cases and 30% to 35% in recurrent and metastatic cases. 4 36 In surviving cases, rehabilitation and physical therapy should be considered part of the treatment program to improve the patient’s neurological status. In the current case, the patient improved markedly after 4 months of physical therapy and rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, rhabdomyosarcoma, non-Hodgkin lymphoma, and Langerhans cell histiocytosis should also be considered in the differential diagnosis [ 8 ]. Concerning the treatment, due to the aggressive behavior of the neoplasm and its great potential to metastasize, treatment should be multimodal and involve radical surgical resection, radiotherapy, and chemotherapy [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…[13] There are five cases of exclusively cervical intramedullary spinal PNETs [Table 1] and 25 primary intradural intramedullary PNETs in the current literature. [71012162022] However, there is only one report of PNET afflicting the cervicomedullary junction. In this paper, we report a case of intraspinal PNET of the cervical spine and cervicomedullary region and review important aspects of this pathology.…”
Section: Introductionmentioning
confidence: 99%